Pengaruh Perputaran Modal Kerja dan DER terhadap ROA pada Perusahaan Sektor Energi yang terdaftar di Bursa Efek Indonesia periode 2020-2023 - Nindi Hastuti Damo; Selvi; Lanto Miriatin Amali (Economic Reviews Journal, 2025)
This study aims to determine and measure the effect of Working Capital Turnover and Debt to equity ratio on return on asset in Energy Sector Companies listed on the Indonesia Stock Exchange for the period 2020-2023. This research is a quantitative study with a sample size of 24 companies using purposive sampling technique with the analysis tool being SPSS version 26. The research results show that Working Capital Turnover partially affects Profitability, Capital Structure partially affects ROA, and both Working Capital Turnover and DER simultaneously affect Profitability. This can be seen from the results of the r-square test, where 68.7% of the Profitability variable can be explained by the Working Capital Turnover and DER. Meanwhile, the remaining 31.3% is influenced and explained by other variables not included in this study.